Simultaneous determination of cytosolic aminoacyl-tRNA synthetase activities by LC-MS/MS - Mendes, Marisa I.; Wolf, Nicole I; Rudinger-Thirion, Joëlle; Lenz, Dominic; Frugier, Magali; Verloo, Patrick; Mandel, Hanna; Manor, Joshua; Kassel, Rachel; Corpeleijn, Willemijn E; van der Rijt, Sanne; Schroor, Elsbeth M; et al. (Nucleic acids research, 2024)
In recent years, pathogenic variants in ARS genes, encoding aminoacyl-tRNA synthetases (aaRSs), have been associated with human disease. Patients harbouring pathogenic variants in ARS genes have clinical signs partly unique to certain aaRSs defects, partly overlapping between the different aaRSs defects. Diagnosis relies mostly on genetics and remains challenging, often requiring functional validation of new ARS variants. In this study, we present the development and validation of a method to simultaneously determine aminoacylation activities of all cytosolic aaRSs (encoded by ARS1 genes) in one single cell lysate, improving diagnosis in suspected ARS1 disorders and facilitating functional characterization of ARS1 variants of unknown significance. As proof of concept, we show enzyme activities of five individuals with variants in different ARS1 genes, demonstrating the usability and convenience of the presented method.